Implementation of Human Resources Management in Improving the Competence of High School Teachers and Employees in Tangerang City - Cepi Berlian, Ujang; Riyanto, Slamet; Sumardi, Sumardi; Salleh, Rosmalily (The International Journal of Education Management and Sociology, 2023)
This research aims to find out the implementation of HRD Management, including the following: Human Resource Planning, HR training, and Human Resource development. The research method uses a qualitative descriptive analysis approach. Data collection techniques include field observations, in-depth interviews, and studying documentation to complete the data. Data analysis uses data reduction, data presentation, and data verification. The research results in the Implementation of HR Management are not focused on the school principal, but also on the people appointed as a team. are: (1). The HR planning system is carried out by analyzing all work activities that must be carried out by all school components. Then it is stated in the Main Duties and Functions, determining positions and jobs, as well as placing personnel in positions according to capacity, capability, work experience, and example (2). The training and human resource development that is carried out is still a formality, limited to whether the training is successful or not, it is not yet oriented towards the impact of the training carried out in changing organizational behavior.